Keeping in Touch with Citizens Online: Social Media Usage in Dutch Local Government - Bram Faber; Tjerk Budding; Raymond Gradus (Tinbergen Institute, 2019)
In recent years, social media has become a major venue for the interplay between citizens and public sector organizations, in order to facilitate corporate dialog. However, not much comprehensive research has been done on how interactivity between local governments and citizens takes shape. Building on earlier work that addresses municipal e-government adoption, this article does empirical work on the ways in which social media is used by all 380 Dutch municipalities. It focuses on social media usage by means of a quantitative assessment through five social media platforms: Twitter, Facebook, LinkedIn, YouTube, and Instagram. In doing so, it sheds light on the interrelations between e-government adoption, social media deployment, and sophistication of use from a local government perspective. Furthermore we identify determinants for the types of social media usage by means of a stages of an e-government model consisting of three phases. We find that more densely populated municipalities with a larger and a higher-educated population use their Twitter account significantly different from their counterparts.
Keywords: D85; 330; social media; municipalities; E-government; usage of Twitter-account